A Morphological Based Prediction of News Stock Market and Money Using Genetic Algorithm - M Vigneshwari, M; Dhanalakshmi, S (International Journal of Computer Sciences and Engineering, 2025)
Globalization has made the Stock Market Expectation (SME) precision more testing also, compensating for the scientists also, other participants in the stock market. Nearby also, global monetary situations along with the company’s monetary quality also, prospects have to be taken into account to progress the expectation accuracy. Genetic Algorithm (GA) has been identified to be one of the overwhelming data mining methods in stock market expectation area. In this paper, we survey distinctive GA models that have been tested in SME with the unique improvement methods utilized with them to progress the accuracy. Also, we explore the conceivable research procedures in this precision driven GA models.